(untitled) (Bangladesh Journal of Medical Science, 2025)
Objectives To determine the probability of developing oncological pathology in individuals with metabolic syndrome (MS) and compare the results with the frequency of tumor development in patients without MS by conducting a retrospective cohort study. Methods This observational retrospective study was conducted between April 2021 and September 2023. According to outpatient charts, the incidence of oncological diseases in 994 patients with MS lasting more than 10 years, and the degree of dependence on its components: abdominal obesity (AO), arterial hypertension (AH), carbohydrate metabolism disorders, dyslipidemia were analyzed1. According to the same parameters, the data of 999 patients without MS who made up the comparison group were analyzed. By the method of cross-tabulation, the odds ratios (OR) of carcinogenesis and 95% confidence intervals (95% CI) were estimated. The SPSS 22.0 program is used for statistical processing of the results of the study. Results The study made it possible to conclude that if a patient has MS, the ten-year risk of developing oncopathology is almost three times higher than in its absence (with MS, an oncoprocess was detected in every 5th patient, in its absence in every 14th). AO, especially grade I, is a risk factor for cancer of various localization. It was revealed that hypertension is a universal risk factor for cancer and aggravates the course of oncological diseases in combination with MS. An important role in the development of cancer processes is played by the age of the patient1. Analysis of the data obtained indicates a decrease in the risk of cancer in people with MS with impaired tolerance to carbohydrates taking metformin. Conclusion MS is a risk factor for the development of oncological diseases of any localization. AO, as the main criterion of MS, is associated with an increased risk of carcinogenesis. Hypertension is the main risk factor for the development of oncological diseases, regardless of the presence or absence of MS. Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 598-605